R Kontribusi Estetika Budaya Melayu terhadap Pendidikan Karakter di Era Global - Reniviolina simanjuntak; Mahdum; Jimmy Copriady; M. Jaya Adi Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Globalization has had a significant impact on socio-cultural development, including in education, such as the demotion of morals and the decline of cultural identity. Local cultural values are often threatened by shifts in current lifestyles, particularly in the character formation of the younger generation. Integrating local cultural aesthetic values, such as Malay culture, into education can be a solution. This article examines the contribution of Malay cultural aesthetics to supporting character education in the global era, specifically how these cultural aesthetic values can strengthen the morals and ethics of the younger generation. Thepurpose of this article is to analyze the contribution of Malay cultural aesthetics to the character formation of students by examining how these aesthetic values can strengthen the morals and ethics of the younger generation. The results of the study indicate that religiousness, politeness, mutual cooperation, and love of country are strongly influenced by Malay cultural aesthetics, which are reflected in art, language, customs, and etiquette. This research emphasizes the importance of preserving and developing local culture as a basis for relevant and contextual character education in the global era.